Optimasi Produksi Inulinase isolat P 12 pada Tepung Umbi Dahlia ( Dahlia variabilis Wild ) dengan Variasi Konsentrasi Nitrogen Organik dan Waktu Inkubasi - Lunggani, Arina Tri; Wijanarka, Wijanarka; Kusdiyantini, Endang (Bioma : Berkala Ilmiah Biologi, 2010)
Efforts to address health problems mainly related to the digestive tract is by consuming one prebiotic, eg fruktooligosakarida (FOS). FOS is a prebiotic that one species can be produced from the hydrolysis of inulin using inulinase enzyme. Isolate P12 is an isolate that has been proven to have high inulinase activity on standard medium inulin production. Inulinase production increase can be done by adding a source of organic nitrogen in the form of yeast extract in medium. The results indicate that the best on the concentration of nitrogen concentration P2 (Yeast extract 0.25%) with the activity of 0.7983 IU, while the best 12-hour incubation time with the activity of 0.7899 IU. Likewise for the best interaction P2 T2 treatment with inulinase activity of 0.9025 IU.